2006
DOI: 10.1159/000092888
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of the Na<sup>+</sup>–Ca<sup>2+</sup> Exchanger, SERCA2a and Calsequestrin after Myocardial Ischemia in the Neonatal Rabbit Heart

Abstract: Background: Neonatal hearts are less susceptible to developing myocardial dysfunction after hypoxia and/or ischemia than adult hearts. Differences in intracellular calcium homeostasis may be responsible for reduced calcium overload of the immature myocardium leading to the observed protection against ischemia. Objective: To assess differences in baseline and post-ischemic gene expression of calcium handling proteins after ischemia in neonatal and adult rabbit hearts. Methods: We used isolated antegrade perfuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…An increase in the intracellular Na + concentration has been shown to correlate with Ca 2+ overload. Enhanced gene expression of this transport system was observed also in the adult failing hearts (Hampton et al 2000) and in ischaemic neonatal hearts (Seehase et al 2006). Experimental evidence supports the proposal that Na + /H + exchange is primarily responsible for Na + influx during hypoxia/ ischaemia.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An increase in the intracellular Na + concentration has been shown to correlate with Ca 2+ overload. Enhanced gene expression of this transport system was observed also in the adult failing hearts (Hampton et al 2000) and in ischaemic neonatal hearts (Seehase et al 2006). Experimental evidence supports the proposal that Na + /H + exchange is primarily responsible for Na + influx during hypoxia/ ischaemia.…”
Section: Discussionmentioning
confidence: 87%
“…In this work, we observed an increase in the NCX1 mRNA levels in both left ventricle and isolated cardiomyocytes from the left ventricle. Enhanced gene expression of this transport system was observed also in the adult failing hearts (Hampton et al 2000) and in ischaemic neonatal hearts (Seehase et al 2006). Increased gene expression of the NCX preserves intracellular calcium homeostasis under conditions of ischaemic and hypoxic stress, thereby attenuating contractile dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…The basal level of [Ca 2+ ] i was increased in ischemic cells with or without GHS treatment. The basal level of [Ca 2+ ] i would reflect the activity of both SERCA2a and RyR2s [35]. Following the recovery of SERCA2a activity by GHS treatment (FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of many Ca 2+ handling proteins is quite long (e.g., up to 2–3 days for SERCA, 9+ h for PLB) (Andersson et al, 2009 ; Teng et al, 2015 ), suggesting that significant changes in protein expression are unlikely within 15 min of ischemia. Indeed, previous studies in the adult rabbit heart indicated that SERCA mRNA levels were decreased following 60 min ischemia, but protein expression remained unchanged (Seehase et al, 2006 ).…”
Section: Discussionmentioning
confidence: 97%